Proposal and Simulation Analysis of Anchor-Less Cooperative Positioning Method Using Multiple Tags and Tag-Mounted Mobile Robot - Mirei Yoshizawa; Taku Shimizu; Sousuke Nakamura (IEEE Access)
Ultra-wideband (UWB) positioning technology positions objects in environments where Global Navigation Satellite System (GNSS) signals are unavailable and is expected to be applied to a wide range of services. However, the challenges associated with anchor installation, such as the need for highly accurate manual positioning and the installation of many anchors, increase the effort and cost of system implementation. Therefore, this paper proposes an anchor-less tag positioning method based on the cooperative use of a mobile robot and multiple tags. This method uses a particle filter to integrate multiple distance measurements obtained via UWB and tag inertial information from Inertial Measurement Units (IMUs). The combination of tag self-calibration by the mobile robot and tag cooperative positioning using the distance between tags enables the omission of anchors. Simulation results show that the proposed method achieves positioning accuracy comparable to conventional anchor-based positioning systems.